2016
DOI: 10.1148/radiol.2016161670
|View full text |Cite
|
Sign up to set email alerts
|

Coronary CT Angiography: Variability of CT Scanners and Readers in Measurement of Plaque Volume

Abstract: Purpose:To determine reader and computed tomography (CT) scan variability for measurement of coronary plaque volume. Materials and Methods:This HIPAA-compliant study followed Standards for Reporting of Diagnostic Accuracy guidelines. Baseline coronary CT angiography was performed in 40 prospectively enrolled subjects (mean age, 67 years 6 6 [standard deviation]) with asymptomatic hyperlipidemia by using a 320-detector row scanner (Aquilion One Vision; Toshiba, Otawara, Japan). Twenty of these subjects underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…where  is the significance level, P is the study power, f is the value of the factor for different values of  and P (f = 10.5 for a P of 90% and an  error of 0.05),  is the interstudy standard deviation,  is the desired percentage difference to be detected, and n is the sample size needed (18). Chest CT reproducibility and sample size were calculated for both a visual and an AI-assisted analysis, as defined above.…”
Section: Discussionmentioning
confidence: 99%
“…where  is the significance level, P is the study power, f is the value of the factor for different values of  and P (f = 10.5 for a P of 90% and an  error of 0.05),  is the interstudy standard deviation,  is the desired percentage difference to be detected, and n is the sample size needed (18). Chest CT reproducibility and sample size were calculated for both a visual and an AI-assisted analysis, as defined above.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the difference in vendors and scan parameters used in baseline and follow-up CCTA scans (see Supplementary data online, Table S2) may have influenced the result. 34,35 However, we adjusted the baseline CACS and PV and the difference in vendors and tube voltages between two CCTA scans in the multivariate analysis and tested the consistency of CCTA in quantitative compositional PV assessment to ensure the reliability and reproducibility of CCTA parameters (see Supplementary data online, Figures S2 and S3). 36 Moreover, because no consensus on the use of serial CCTA for CAD monitoring currently exists, 6 an observational study such as the PARADIGM study provides a unique opportunity to evaluate the correlation between CACS progression assessed by CAC scans and the change in plaque burden.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published systematic review implies that CCTA has a potential role in assessment on the response of statin therapy on plaque volume and composition [40]. Such serial plaque assessments demand usage of the same software [41, 42]. In our study, plaque assessments were performed with a software previously shown to have a high degree of inter-observer variability on calcified and mixed lesions [23].…”
Section: Discussionmentioning
confidence: 99%